The Efficacy and Hemorheological Indexes of Ginseng and Its Active Components for Patients with Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis. (17th February 2023) - Xia, Yawen; Han, Hongkuan; Gu, Renjun; Tao, Ruizhi; Lu, Keqin; Sun, Zhiguang; Shen, Sanbing; Wang, Aiyun; Lu, Yin
Abstract : Background . Non-small cell lung cancer (NSCLC) is still a slightly less orphan disease after immunotherapy, and routine treatment has low efficiency and adverse events. Ginseng is commonly used in the treatment of NSCLC. The purpose of this study is to assess the efficacy and hemorheological indexes of ginseng and its active components in patients with non-small cell lung cancer. Methods . A comprehensive literature search was performed in PubMed, the Cochrane Library, Medline (Ovid), the Web of Science, Embase, CKNI, Wan Fang, VIP, and SinoMed up to July 2021. Only randomized controlled trials evaluating ginseng in combination with chemotherapy versus chemotherapy alone in NSCLC patients were included. Primary outcomes included patients' condition after using ginseng or its active components. Secondary outcomes included changes in immune cells, cytokines, and secretions in serum. Data were extracted by two independent individuals, and the Cochrane Risk of Bias tool version 2.0 was applied for the included studies. Systematic review and meta-analysis were performed by RevMan 5.3 software. Results . The results included 1480 cases in 17 studies. The results of the integration of clinical outcomes showed that the treatment of ginseng (or combination of ginseng with chemotherapy) can improve the quality of life for patients with NSCLC. Analysis of immune cell subtypes revealed that ginseng and its active ingredients can upregulate the percentages of antitumor immunocyte subtypes and downregulate the accounts of immunosuppressive cells. In addition, a reduction of the inflammatory level and an increase of antitumor indicators in serum were reported. Meta-analysis showed that Karnofsky score: WMD = 16, 95% CI (9.52, 22.47); quality-of-life score: WMD = 8.55, 95%CI (6.08, 11.03); lesion diameter: WMD = −0.45, 95% CI (−0.75, −0.15); weight: WMD = 4.49, 95% CI (1.18, 7.80); CD3 + : WMD = 8.46, 95% CI (5.71, 11.20); CD4 + : WMD = 8.45, 95% CI (6.32, 10.57)+; CD8 + : WMD = −3.76, 95% CI (−6.34, −1.18); CD4 + /CD8 + : WMD = 0.32, 95% CI (0.10, 0.53); MDSC: WMD = −2.88, 95% CI (−4.59, −1.17); NK: WMD = 3.67, 95% CI (2.63, 4.71); Treg: WMD = −1.42, 95% CI (−2.33, −0.51); CEA: WMD = −4.01, 95% CI (−4.12, −3.90); NSE: WMD = −4.00, 95% CI (−4.14, −3.86); IL-2: WMD = 9.45, 95% CI (8.08, 10.82); IL-4: WMD = −9.61, 95% CI (−11.16, −8.06); IL-5: WMD = −11.95, 95% CI (−13.51, −10.39); IL-6: WMD = −7.65, 95% CI (−8.70, −6.60); IL-2/IL-5: WMD = 0.51, 95% CI (0.47, 0.55); IFN- γ : WMD = 15.19, 95% CI (3.16, 27.23); IFN- γ /IL-4: WMD = 0.91, 95% CI (0.85, 0.97); VEGF: WMD = −59.29, 95% CI (−72.99, −45.58); TGF- α : WMD = −10.09, 95% CI (−12.24, −7.94); TGF- β : WMD = −135.62, 95% CI (−147.00, −124.24); TGF- β 1: WMD = −4.22, 95% CI (−5.04, −3.41); arginase: WMD = −1.81, 95% CI (−3.57, −0.05); IgG: WMD = 1.62, 95% CI (0.18, 3.06); IgM: WMD = −0.45, 95% CI (−0.59, −0.31). All results are statistically significant. No adverse events were reported in the included articles. Conclusion . It is a reasonable choice to use ginseng and its active components as adjuvant therapy for NSCLC. Ginseng is helpful for NSCLC patients' conditions, immune cells, cytokines, and secretions in the serum.